B10 Cell Frequencies and Suppressive Capacity in Myasthenia Gravis Are Associated with Disease Severity - Yi, John S.; Russo, Melissa A.; Massey, Janice M.; Juel, Vern; Hobson-Webb, Lisa D.; Gable, Karissa; Raja, Shruti M.; Balderson, Kristina; Weinhold, Kent J.; Guptill, Jeffrey T. (Frontiers in Neurology, 2017)
Myasthenia gravis (MG) is a T cell dependent, B cell mediated disease. The mechanisms for loss of self-tolerance in this disease are not well understood, and recently described regulatory B cell (Breg) subsets have not been thoroughly investigated. B10 cells are a subset of Bregs identified by the production of the immunosuppressive cytokine, interleukin-10 (IL-10). B10 cells are known to strongly inhibit B- and T-cell inflammatory responses in animal models and are implicated in human autoimmunity. In this study, we examined quantitative and qualitative aspects of B10 cells in acetylcholine receptor autoantibody positive MG (AChR-MG) patients and healthy controls. We observed reduced B10 cell frequencies in AChR-MG patients, which inversely correlated with disease severity. Disease severity also affected the function of B10 cells, as B10 cells in the moderate/severe group of MG patients were less effective in suppressing CD4 T-cell proliferation. These results suggest that B10 cell frequencies may be a useful biomarker of disease severity, and therapeutics designed to restore B10 cell frequencies could hold promise as a treatment for this disease through restoration of self-tolerance.